PERANCANGAN SISTEM REKAYASA LINGKUNGAN SMART GREENHOUSE MENGGUNAKAN FUZZY LOGIC CONTROLLER PADA TANAMAN CABAI - Luthfi Gani Hakim; Aghus Sofwan; Aris Triwiyatno (Transient: Jurnal Ilmiah Teknik Elektro, 2020)
In Indonesia, chili can be planted in various areas, both in the fields or moor, sea coast, and mountains. However, chili productions is not good, it is only increasing little by little and is not proportional to the rapid market needs. Efforts are neede to encourage the advancement of technology so that chili cultivation is more efficient. Smart Greenhouse is one of technology that can be used to help humans produce their own chili plants. The concept of smart greenhouse is the integration of data into the internet that connected to a accessed database using an android smartphone application compatible with features such as reporting, updating feeds, and controlling. DHT 22 is used as a sensor for reading temperature and humidity in Greenhouse, Moisture Sensor is a sensor for reading soil moisture. Fuzzy Logic Controller is applied for controlling temperature, humidity and soil moisture in Greenhouse. From the testing that has been done, Fuzzy Logic Controller that is applied can reach the reference temperature at 27oC in 465 seconds, the humidity control can reach 80% in 150 seconds and the soil moisture control can reach 80% in 10 seconds.